The Elimination of ‘Mind - Body’ Dualism in Nietzsche’s Anthropology: From ‘Mind’ to ‘Will’ - Paul Rohan, J.C. (National Seminary of Sri Lanka, Ampitiya, Kandy, 2022)
Friedrich Nietzsche (1844-1900) had a prominent place in shaping the thinking pattern of the 20th century, especially in the Continental Europe. His anthropology is based on creating a ‘new man’ who would come out of all the barriers of morality, religion and other value systems. This new man is called by other thinkers as ‘Nietzschean Man’ who has a total contrast of the characteristics of the ‘Christian Man’. This paper is not comparing both of them; rather the primary characteristics of ‘Nietzschean Man’ is dealt with to show that Nietzsche’s anthropology is overwhelmed with ‘will’ in contraposition to the traditional Christian anthropology which had been substantially ‘mind’ centered. Nietzsche attacked the dualistic view of the human being as body and mind and affirmed that both are one. According to him, human life is driven fundamentally by a will-to-power, a drive more powerful and more primal than the pleasure instinct. Will-to-power is what Nietzsche identifies as the most basic driving force of all living beings. The concept of the will-to-power, offers a universal perspective on human nature. Nietzsche’s attacks on the ‘Christian Man’ has to be understood as his attempt to create a new man based on his new anthropology eliminated from the doom of the dualism of mind and body.
Keywords: Nietzschean man; Will-to-power; Power-politics; Voluntarism; Dualism; Unpleasurable tension